Thromboembolic events associated with endovascular treatment of cerebral aneurysms. (8th January 2011) - Altay, Tamer; Kang, Hee I; Woo, Henry H; Masaryk, Thomas J; Rasmussen, Peter A; Fiorella, David J; Moskowitz, Shaye I
Abstract : Objective: To evaluate the rate of peri-procedural thromboembolic events after the endovascular treatment of cerebral aneurysms. The rate of diffusion-positive lesions was assessed in relation to selected procedural and technical factors. Methods: 184 patients treated with coil embolization (198 total procedures) between July 2004 and February 2007 were included. In 65, the procedure was coiling alone; in 55, coiling with balloon remodeling; in 48, coiling with Neuroform stenting; and in 30, coiling, Neuroform stenting and balloon remodeling. All patients underwent a routine diffusion weighted magnetic resonance imaging (DWI) within the 72 h after the intervention for the detection of ischemic complications. Results: Regardless of the technique used, thromboembolic complications were more common (p<0.0001) in patients with ruptured aneurysms (33/65, 51%) than in those with unruptured aneurysms (40/133, 30%). Balloon remodeling tended to be associated with a lower rate of DWI positivity than the other techniques. Younger patients (≤60) with unruptured aneurysms had the lowest rates of DWI lesions regardless of the technique used. Conclusion: In this study, peri-procedural DWI-positive lesions occurred in approximately one-third of all cases. These were threefold more common in the setting of ruptured aneurysms. Adjunctive devices did not increase the rate of ischemic events. On the contrary, there was a trend toward fewer DWI abnormalities in the procedures in which balloon remodeling was employed. This may, in part, be related to the application of the conglomerate coil mass technique of balloon remodeling.